Road Performance Analysis (Case Study: Jl. Kakialy Ambon City) - Selly Metekohy; Juliet G. Metekohy (Jurnal Indonesia Sosial Teknologi, 2023)
The number of residents in Ambon City every year has increased, therefore the number of increases in vehicle volume is directly proportional to the number of population growth, and in line with the increasing problem of traffic congestion. One of the traffic jams that occur in Ambon City is on the Kakialy road, which is caused by side obstacles due to unattended vehicle parking on the road, especially during rush hour or peak hours (during school and after school or commuting and returning from work). The existence of community facilities such as shops, fast food areas, hotels, and residential areas is also one of the triggers for road body parking which causes congestion on the Kakialy road section. Therefore, this study was conducted to find out how the performance of the Kakialy road section during peak and normal hours. The method used is a descriptive survey that uses data collection techniques in the form of observation and documentation studies for the calculation of capacity and speed on urban roads using the Indonesian Road Capacity Manual (MKJI) method. The results of data analysis show that the capacity of peak hours at 12.00-13.00 WIT) is 18,721 junior high school/hour and normal hours at 16.00-17.00 WIT is 15,037.8 junior high school/hour, with a vehicle density value (DS) at peak hours of 0.59. The average side resistance data in peak hours has a weighted frequency of 366.6 SMP/hour so it belongs to the medium side resistance class (M), and the average side resistance in normal hours has a weighted frequency of 148.7 SMP/hour, including the low side resistance class (L). So that after going through the calculation analysis process, it is concluded that the vehicle density value (DS) at peak hours (12.00 – 13.00 WIT) is 0.59 and is categorized in Level Of Service (LOS) C which means medium performance. While the vehicle density value (DS) during normal hours (16.00 – 17.00 WIT) is 0.45 and is categorized in Level Of Service (LOS) B which means good performance.